Patents and the Agricultural Industry - Sadler, Pauline (School of business law, curtin business school, curtin university of technology, 2007)
This article gives a brief overview of the patent regime in Australia, with particular emphasis on its relevance to the agricultural industry. The article begins with a background to the patent regime in Australia. It then examines ownership, validity, exceptions to patentability, the application process, the specification and revocation. Relevant provisions of the Patents Act 1990 (Cth) are examined as necessary, as are relevant regulations in the Patents Regulations 1991 (Cth). Cases discussed include National Research Development Corp v Commissioner of Patents (1959) 102 CLR 252 and Van der Lely NV v Bamfords Ltd [1963] RPC 61.